Islamophobia and Islamic moderation - Spahic, Omer (Dar Al Wahi Publication, 2022)
It is undeniable that Islamophobia and Islamic moderation (wasatiyyah) are two of the most widely used and abused concepts nowadays. There are no agreed-upon definitions. Thus, they are used predicated on contexts, prevalent sentiments and interests. Not only the friends and foes of Islam and Muslims, but also Muslims themselves, are at fault. More often than not, people are guided by expediency rather than principle, and by unreasonableness rather than rationality. This book aims to shed more light on the two concepts, trying to explain more points where they simultaneously congregate and part company. The book is a collection of twenty two chapters, which loosely constitute a whole. The whole could be perceived in terms of examining diverse aspects of each of Islamophobia and Islamic moderation and finding a common thread to most of them. The book discusses such themes as the meaning, origins and evolution of Islamophobia; Muslims and Western civilization; Christian-Muslim polemics and the role of John of Damascus; the contributions of Riccoldo da Monte di Croce and Martin Luther to Islamophobia; an example of Western unprejudiced views on Islam; Prophet Muhammad (pbuh) and fighting (Islamic ethics of war); the meaning and significance of Islamic moderation (wasatiyyah); the Srebrenica genocide; the notions of modernity, Islamic unity, peace, justice, happiness, might, and the Qur’an as the ultimate source of history.